Tour Guide’s Service at Aceh Tsunami Museum - Nurul Kamaliah; Helmiyadi Helmiyadi; Menalisa Menalisa (Linguistic, English Education and Art (LEEA) Journal, 2019)
Seeing the important role of services for the advancement of tourism, this research needs to be carried out with the aim of analyzing the understanding of guides about the competence of a guide, services provided to tourists, the obstacles faced by guides in providing services to tourists, and the efforts made by guides and museum institutions to overcome the obstacles encountered. Respondents in this study were guides and chief of guides at the Aceh Tsunami Museum. This research uses qualitative methods with descriptive data. The data in this study uses the techniques of documentation study, interviews and observations. Then the data are analyzed using several stages, namely data reduction, data presentation, and data verification or drawing conclusions. The results of the research are the Aceh Tsunami Museum placed the competence and services of tour guides as the spearhead of tourist satisfaction, although there is a deficiency that the tour guides have not received adequate seminars or training as the way to support their profession. Conclusion, the guides got many improvements related to their English competence dominantly by learning directly from tourists, learning from experience, learning self-taught, and considering tourists as friends. Keywords: services, tour guides, aceh tsunami museum